THE EXTENT OF THE IMPACT OF QUALITY COSTS ON THE EFFICIENCY OF FINANCIAL PERFORMANCE AN APPLIED TO STUDY IN THE IRAQI COMPANY FOR THE MANUFACTURE AND TRADE OF CARTONS (IICM) (World Economics and Finance Bulletin, 2022)
The research aims to measure the impact of quality costs on the efficiency and evaluation of financial performance in the Iraqi company for production. First, to explain the research problem and achieve its objectives, the descriptive analytical approach was adopted, as (50) questionnaires were distributed to the sample members (accountants, cost centre accountants, production line managers, sales centre managers, and financial analysts). Then, using the scale of the simple linear regression model, the research hypotheses were tested, and the research reached the most important conclusions, namely: the application of quality costs and exemplary implementation has become a crucial indicator of the improvement of the company's performance in general and financial performance in particular. The most important recommendations: The need to apply quality costs to ensure continuous improvement of products and to discover and analyze the costs of defective products and their treatment, thus ensuring the quality of products and finding ways to reduce these costs
Keywords: Quality; evaluation; preventive; internal